Liberdade em Alexis de Tocqueville - Cleto, Marcelo de Souza (2005)
The aim of the present work is to look over Alexis de Tocqueville s political-philosophical thoughts. At first, the philosophical influence on the author s intellectual knowledge is approached in a way to show his debate with the tradition. Secondly, questions related more directly to democracy are mentioned having references based on the clear concepts of the author on democratic government, society and policy. The controversial relationship between political freedom and equality established within the democratic societies is one of the most significant aspects shown by Tocqueville. Furthermore, the work goes on analyzing the democratic society in contrast with the aristocracy. Tocquevillian legacy to the history of political ideas has reached a fundamental status as one of the theories that supports the modern liberalism, and with the advent of Modernism, more specifically the problems concerning to the human liberty. Tocqueville presents himself as an interpreter of the contradictions related to liberty and democracy.At last, the democratic proposals presented by the author known as the center point of the whole controversy between democracy and its relationship with both the equality and liberty. The demonstration of the freedom concept as an understood fact of Tocquevillian readings supports this research. This comprehension of freedom in taking such diverse qualities, will clearly enable the understanding on how liberty can be endangered by man, and trapping him at the same time. Thus, it s necessary that liberty be constantly under attention and surveillance to face the threats of an individualism that could risk the democracy victory.